ChemInform Abstract: Regioselective Alkylation Reactions of 2, 4‐Diphenyl‐3H‐1‐benzazepine Give Either 3‐Alkyl‐3H‐1‐benzazepines or 1‐Alkyl‐1H‐1‐benzazepines. Issue 2 (January 2015) - Ko, Allen; Lam, Aaron; Li, Jeffrey; Greer, Edyta M.; Szalda, David J.; Karimi, Sasan; Subramaniam, Gopal; Ramig, Keith
Abstract Deprotonation of benzazepine (I) followed by reaction with alkyl halides or tosylates give either products of alkylation at C3 or at the nitrogen as well as mixtures of both types of products.